Areas of professional life and job satisfaction of nurses - Tomaszewska, Katarzyna; Kowalczuk, Krystyna; Majchrowicz, Bożena; Kłos, Alicja; Kalita, Krzysztof (Frontiers in Public Health, 2024)
Introduction Job satisfaction among nurses is closely related to work environment as well as organizational and professional commitment. Satisfaction is a concept derived from Latin, where “satis” means “enough,” as much as is needed to fully satisfy expectations, needs, aspirations, in such a way that there is no room for complaint. Job satisfaction, on the other hand, is formulated as a positive attitude of employees toward the duties of the job, the work environment and other employees. The aim of this paper was to demonstrate how the different areas of nurses’ professional life, i.e., workload, control, rewards, community, sense of justice and values, correlate with their perceived job satisfaction. Materials and methods A cross-sectional study was conducted in a group of 509 nurses working in a public hospital in Poland. Data were collected using a survey questionnaire, which consisted of a section containing sociodemographic data and standardized instruments: The Minnesota Satisfaction Questionnaire (MSQ) and The Areas of Worklife Survey (AWS) developed by Maslach and Leiter. Correlations were made using Spearman’s rho coefficient. The calculations also used stepwise linear regression analysis after checking certain assumptions, including checking the assumption of normality of residuals and the Durbin-Watson Test. Results The mean score for the 20 items of the MSQ questionnaire ranged from 3.05 to 3.43 on a 5-point Likert scale. Support from the interdisciplinary team, which concerned assessing the quality of the social environment in the workplace, cooperation and showing positive feelings received the highest rating among respondents (3.51 ± 0.76). The sense of fair treatment at work averaged 3.26 ± 0.58. The area of value conflict within the organization itself or between the employee’s values and those of the organization, respondents rated an average of 3.26 ± 0.65. The mean score for all areas of professional work in the surveyed group was 3.09 ± 0.45. Conclusion As satisfaction in particular areas of work life increases, so does the level of satisfaction in such aspects of work as achievement and a sense of fairness. The higher the level of satisfaction in the area of control, the more the sense of satisfaction with independence increases. The higher the satisfaction of respondents in the areas of values, workload and control, the higher the level of satisfaction with working conditions occurs.